Association between Slow and Rapid Weight Gain before 36 Weeks of Corrected Age and 6-Year-Developmental Quotient in Infants Born at <26 Weeks of Gestation - Hotta, Masashi; Hirata, Katsuya; Hirano, Shinya; Wada, Kazuko (American Journal of Perinatology, 2024)
The postnatal growth of preterm infants is influenced by various factors; however, the association between growth and long-term outcomes in extremely preterm infants remains unclear. Therefore, we aimed to determine the association between 6-year development and body weight (BW) at 36 weeks of corrected age (CA) in extremely preterm infants.We conducted a retrospective observational study including extremely preterm infants born at < 26 weeks of gestation. We defined the key standard deviation score (SDS) using BW at birth and evaluated the association between BW-related values at 36 weeks of CA and the 6-year developmental quotient (DQ).This study included 90 infants. The absolute difference between changes in the BW SDS from birth and the median changes in DQ ≥ 85 infants was significantly greater in infants with a DQ < 85 than ≥85 (median [interquartile range]: 0.80 [0.29, 1.31] vs. 0.34 [0.13, 0.55]; p = 0.001). After adjustment by the logistic regression analysis for DQ < 85, the absolute difference was statistically significant (odds ratio: 4.99, 95% confidence interval: 1.71–14.5). The correlation coefficient between the absolute difference and DQ was −0.35 (p < 0.001). There were no significant associations between a DQ < 85 and SDS or changes in SDS from birth.For infants born at <26 weeks of gestation, slow and rapid weight gain were associated with a low 6-year DQ when using values representing individual body sizes at birth. Individual backgrounds should be considered to avoid both slow and rapid weight gain for the growth management of these infants for at least up to 36 weeks of CA. Further research is needed to determine which body size has a positive impact on the long-term outcomes of infants.
Keywords: extremely preterm infants; growth and development; neonate; preterm infants; precision nutrition; precision medicine